The Prospect of Artificial Intelligence in Dentistry - Banerjee , Madhulika; Meetika; Sharma, Rajat; Gahlot, Deepshikha; Grover , Ramanjeet Kaur; Sihani, Komal (Medical Research and Its Applications Vol. 6, 2024)
Artificial intelligence (AI) is one of the fields of technology that is expanding tremendously in a short span of time. AI in the healthcare sector is evolving and has a promising future. Key applications in dentistry include patient care, diagnostics and treatment guiding, and administrative tasks. As a result, this AI system enables dentists to become acquainted with this cutting-edge technology, as dentistry will soon combine artificial intelligence and dentistry in an incredible way. The need for accurate patient records, and dependable robotic surgery treatment has increased the use of these software technologies in helping dentists diagnose and treat patients in a way that is both satisfying and practical. This chapter aims to highlight the role of artificial intelligence in dentistry, yet technical advancements like this are still in their early stages.